Minimally Invasive Bilateral Lung Resections and CABG through 5 Ports. (13th December 2018) - Asemota, N.; Rouhani, M. J.; Harling, L.; Raubenheimer, H.; De Souza, A. C.; Lim, E.
Abstract : Minimal access surgery is increasingly popular to reduce postoperative morbidity and enhance recovery. We present a case of a patient who underwent bilateral minimally invasive thoracic and cardiac surgery. An 81-year-old woman was diagnosed with T1aN0M0 left upper lobe small-cell lung cancer and underwent single-port left video-assisted thoracoscopic surgery (VATS) upper lobectomy in 2016. She developed a contralateral right lower lobe nodule and underwent a single-port right VATS wedge resection of the lower lobe nodule, subsequently confirmed as necrotising granulomatous inflammation with acid-fast bacilli, consistent with previous tuberculosis (TB) infection. On postoperative day 1, she had an episode of self-reverting ventricular tachycardia and bradycardia. Subsequent myocardial perfusion scan and coronary angiogram showed significant LV dysfunction and severe coronary artery disease with a left main stem (LMS) lesion. After agreement at MDT, an Endo-ACAB (endoscopic atraumatic coronary artery bypass grafting) was performed, via 3 ports, with the left internal mammary artery anastomosed to left anterior descending artery. She recovered well postoperatively and was discharged. Multiple sequential minimally invasive procedures are now routine and can be performed safely in patients with a complex combination of pathologies. In this case, bilateral single-port (anatomic and nonanatomic) lung resections were undertaken followed by coronary revascularisation with a total of 5 minimal access ports.